TINJAUAN YURIDIS TERHADAP UPAYA PENENTUAN NASIB SENDIRIANTARA CRIMEA DENGAN UKRAINA - Yunita Sari; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Inthe internationallawthere is aprinciple ofself-determination, which is part ofHuman Rights, but theprinciple ofthe right to determinetheir ownis still acomplicatedissue. Bothat the level ofthe conceptualandlegaldebateand at the levelof realpolitics in manyregions of the world. The purpose of this research are, first to know self-determination ofthe peopleCrimeain accordancewith therulesof International Law, secondto know legality ofthe referendum conductedby theCrimeanresidents whosupport theseparationof the UkraineandjoinRussia, third to know Howothercountriesrecognitionof theresults of the referendumcitizensof Crimea. This case study further discuses about the principles of law and comparison of law. Source of data used are secondary data source of obtained from the literature, among others,includeofficial documents, books, research resultsin the form ofreportsandso on. The conclusion of theresearchare,firstSelf-determinationis aprincipleembodied ininternationallaw, wheresuch rightshave been formulatedinthe UN Charter. Self-determinationreferendumconductedby means ofCrimeahas a goaltosecedefromUkraineandjoinRussia. Second, theimplementation of thereferendumshouldcomply withprovisionsof Crimeain accordancewith the principlesof international law.Third, recognitionininternationallawis afairlycomplexissuebecauseonceinvolvelegaland politicalissues. in the case ofCrimearecognitionin the reviewbased on thedeclarativetheory. Keywords: Effort-Determination-fate-Self-Crimea